Maritime Politics and Policy in the City of Ships - Timm, Christopher; Page, Kelly; Cyr, Catherine (Maine Policy Review, 2023)
Along the Kennebec River, over 2,500 vessels were launched in Bath, “The City of Ships,” from the 18th century to the present day. Shipbuilding transformed the town—its economy, global prominence, and architecture. This article examines Bath as a case study of the role of politics and policy in Maine’s maritime history. Shipbuilding positioned Bath at the center of national politics and at the center of the nation’s imperial ambitions, while also heavily influencing its architectural fabric and workforce.
Keywords: City of Bath; shipbuilding industry; maritime history